Longitudinal Variations of CDC42 in Patients With Acute Ischemic Stroke During 3-Year Period: Correlation With CD4+ T Cells, Disease Severity, and Prognosis - Cheng, Xiao; Ye, Jianxin; Zhang, Xiaolei; Meng, Kun (Frontiers in Neurology, 2022)
Objective: Cell division cycle 42 (CDC42) modulates CD4+ T cell differentiation, blood lipid, and neuronal apoptosis and is involved in acute ischemic stroke (AIS) pathogenesis; however, the clinical role of CDC42 in AIS remains unanswered. Herein, this study aimed to evaluate CDC42 expression during a 3-year follow-up period and its correlation with disease severity, T helper (Th)1/2/17 cells, and the prognosis in AIS patients. Methods: Blood CDC42 was detected in 143 AIS patients at multiple time points during the 3-year follow-up period and in 70 controls at admission by RT-qPCR; besides, blood Th1, Th2, Th17 cells and their secreted cytokines (IFN-γ, IL-4, IL-17A) in AIS patients were detected by flow cytometry and ELISA, respectively. Results: CDC42 was reduced in AIS patients compared with controls (P<0.001). CDC42 was negatively correlated with NIHSS score (P<0.001); meanwhile, it was positively associated with Th2 cells and IL-4 but negatively correlated with Th17 cells and IL-17A in AIS patients (all P<0.050). CDC42 was decreased from admission to 3 days and gradually increased from 3 days to 3 years in AIS patients (P<0.001). During 3-year follow-up, 24 AIS patients recurred, and 8 patients died. CDC42 at 3 days, 7 days, 1 month, 3 months, 6 months, 1 year, 2 years, and 3 years was decreased in recurrent patients than non-recurrent patients (all P<0.050). CDC42 at 7 days (P=0.033) and 3 months (P=0.023) was declined in dead patients reported to survived patients. Conclusion: CDC42 is used as a biomarker to constantly monitor disease progression and recurrence risk of AIS patients.